The effect of compensation and work environment on employee’s job satisfaction - Tarmidi, Didi; Hendiarto, R Susanto; Sunjana, Sunjana (Institute of Computer Science (IOCS), 2024)
This study aims to determine how the description of compensation, work environment, and employee job satisfaction, as well as to determine how compensation and work environment affect the job satisfaction of employees of XYZ Private Hospital. The factors tested in this study were compensation and the work environment as independent variables, while job satisfaction was a dependent variable. The research methods used in this study are descriptive and verification methods. The population in this study was employees at XYZ Private Hospital. The sampling technique used in this study is Purposive Sampling and the size of the samples in this study is calculated by slovin formula, so the total number is 93 respondents. The analysis methods used in this study are some linear regression analysis using SPSS25 for Windows. The results of this study showed that compensation and work environment have an effect on employee job satisfaction at XYZ Private Hospital. The amount of compensation and work environment influenced employee job satisfaction by 49.2%.